2010
DOI: 10.1007/s10336-010-0500-5
|View full text |Cite
|
Sign up to set email alerts
|

Advanced departure dates in long-distance migratory raptors

Abstract: International audienceEvidences for phenological changes in response to climate change are now numerous. One of the most documented changes has been the advance of spring arrival dates in migratory birds. However, the effects of climate change on subsequent events of the annual cycle remain poorly studied and understood. Moreover, the rare studies on autumn migration have mainly concerned passerines. Here, we investigated whether raptor species have changed their autumn migratory phenology during the past 30 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 20 publications
7
35
1
Order By: Relevance
“…However, findings from the current study are broadly comparable to numerous works that have noted correlations between shifting migration phenology and climate change (Gordo 2007). The variable responses we observed in autumn passage timing supports previous heterogeneous findings on migratory shifts in postnuptial movements for other species (Jenni & Kéry 2003, Thorup et al 2007, Filippi-Codacciuoni et al 2010, Van Buskirk 2012. Other researchers have noted distinct increases in temperature for Western Europe during the latter part of the 20th century, followed by a period of relative cooling (Jaffré et al 2013) and these trends are in concordance with changes in temperature across the northern hemisphere (IPCC 2007, Lawrimore et al 2011.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, findings from the current study are broadly comparable to numerous works that have noted correlations between shifting migration phenology and climate change (Gordo 2007). The variable responses we observed in autumn passage timing supports previous heterogeneous findings on migratory shifts in postnuptial movements for other species (Jenni & Kéry 2003, Thorup et al 2007, Filippi-Codacciuoni et al 2010, Van Buskirk 2012. Other researchers have noted distinct increases in temperature for Western Europe during the latter part of the 20th century, followed by a period of relative cooling (Jaffré et al 2013) and these trends are in concordance with changes in temperature across the northern hemisphere (IPCC 2007, Lawrimore et al 2011.…”
Section: Discussionsupporting
confidence: 81%
“…Black Storks and Honey Buzzards both advanced their migratory timing. Filippi-Codacciuoni et al (2010) reported an advance in migration of 3.39 days for Honey Buzzards. Our estimates of an advance in passage timing of 3 days for this species is in agreement with this observation and supports other studies which report advancing passage dates in European short-distance soaring birds (Jaffré et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant difference in the map time trend over 48 years was observed between the two migration categories (MannWhitney U test, U = 66.0, P = 0.928). This contradicts other findings, where LD migrants had a tendency to advance their autumn migration times whereas SMD migrants had a tendency to migrate later (Jenni and Kéry 2003;Tøttrup et al 2006;Filippi-Codaccioni et al 2010;Fig. 10 Shifts in map time in 26 species on Helgoland from 1960 to 2008 that were trapped with constant effort (asterisks indicate significant changes according to linear regression, P (2) \ 0.05) Fig.…”
Section: Climate Change Related Alterations In Phenologycontrasting
confidence: 75%
“…Conclusions drawn in the limited literature on climatic effects on avian autumn migration remain mixed (Mezquida et al 2007;Van Buskirk et al 2009;Filippi-Codacciuoni et al 2010), and several studies have failed to find support for any of the proposed hypotheses (Mills 2005;Gordo and Sanz 2006;Adamik and Pietruszkova 2008).…”
Section: Introductionmentioning
confidence: 91%